1986
DOI: 10.1007/bf02456284
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal diagnosis of pulmonary tumours: report of two cases

Abstract: We report two cases of antenatal diagnosis of pulmonary tumours. In one case a bronchogenic cyst was connected with the bronchopulmonary tree and grew rapidly after birth. Thanks to the antenatal diagnosis, it was resected before any complication appeared. In the second case, congenital cystic adenomatoid malformation of the lung was associated with fetal anasarca. Initially cyst aspiration was carried out; then long-term drainage was attempted. These cases illustrate the impact of antenatal diagnosis on perin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…There have been sev eral reports on aspiration and shunt opera tion. Aspiration was not effective as 3 of 4 cases showed re-expansion [3][4][5][6], while a cystamniotic shunt was reported to be effective. In particular, the first report was by Clark et al [5] who reported on the successful treat ment of a hydrops patient by using the double pigtail catheter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been sev eral reports on aspiration and shunt opera tion. Aspiration was not effective as 3 of 4 cases showed re-expansion [3][4][5][6], while a cystamniotic shunt was reported to be effective. In particular, the first report was by Clark et al [5] who reported on the successful treat ment of a hydrops patient by using the double pigtail catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Mu cus-producing cells are seen not only along the wall, but also in the gland-like structures be neath the wall. Focally increased elastic tissue in the cystic wall and absence of inflammation are also characteristic pathological findings [2], Due to the progress in antenatal diagnosis, several cases of CCAM were diagnosed antenatally, and some pioneers have been trying to treat them in utero [3][4][5][6][7], Here, we are going to report 12 cases of CCAM and discuss the strategy of an ideal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The authors did not feel that thoracentesis contributed to the outcome because of the rapid reaccumulation of cyst fluid [3]. The second example was in a fetus at 26 weeks ges tation exhibiting hydrops and right mediasti nal shift secondary to a large multiloculated cystic mass [4]. Thoracentesis was performed and 120 ml clear fluid was removed.…”
Section: Discussionmentioning
confidence: 99%
“…Two cases of intrauterine thoracentesis for cystic adenomatoid malformation have been described previously [3,4], The first was per formed at 34 and 36 weeks gestation with 50 ml removed at each aspiration. Fluid rap idly reaccumulated within 16 h. The infant was born vaginally at 37 weeks gestation and did well following immediate thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation